To the problems of revitalization of public spaces in Eastern Bloc housing estates - Veselý, Martin; Vacek, Lukáš (Journal of Architecture and Urbanism, 2013)
The article is a contribution to the discussion about the revitalizations of over-dimensioned and characterless public spaces in housing estates areas in the Eastern Bloc. The Central Park in Southern Town I – the largest housing estate in Prague – is a significant example of such public space.The article presents the main results of two different but complementary analysis of the Central Park. Analysis “from bellow” (the user's perspective) is based on the results of anthropological research in the area. Analysis “from above” is based on personal experience of an urban planner.According to the authors only the triangulation of anthropological and architectural/urban planning methods of reading place allows to come near to complex understanding of place, its character and identity.The authors point out the importance of participation of the users in the revitalizations, which is an important condition of the broad acceptance of the result. Most of the Czech municipalities are still mistrustful of participatory processes. That brings many unnecessary problems.